Analisis Kesalahan Siswa dalam Menyelesaikan Soal Cerita Persamaan Nilai Mutlak Berdasarkan Kriteria Watson Kelas X SMA Negeri 1 Sarudu - Musdalifah Musdalifah; Bakri M; Sutji Rochaminah (Media Eksakta, 2023)
This study aims to obtain a description of the types of errors made by class X students of SMA Negeri 1 Sarudu in solving absolute value equation word problems based on Watson's criteria. This type of research is descriptive research with a qualitative approach. The subject of this research was taken by three students out of 18 students consisting of two students who made many mistakes and one who made few mistakes. The results of this study were (1) the types of errors made by subjects who made the first mistake in solving absolute value equation word problems were inappropriate procedure, and omitted conclusion. (2) the type of mistakes made by subjects who make a lot of second mistakes in solving the absolute value equation story problem is inappropriate data, undirected manipulation, and omitted conclusion. (3) the types of mistakes made by the subjects who make few mistakes in solving the absolute value equation story problem are inappropriate procedure.